A novel nuclear forensic tool involving deposit type normalized rare earth element signatures. (6th July 2017) - Spano, Tyler L.; Simonetti, Antonio; Wheeler, Thomas; Carpenter, Grace; Freet, Devonee; Balboni, Enrica; Dorais, Corinne; Burns, Peter C.
Abstract: Identifying the provenance of uranium‐rich materials is a critical objective of nuclear forensic analysis. Rare earth element (REE) distributions within uranium ores are well‐established forensic indicators, but quantifying and correlating trace element signatures for U ores to known deposits has thus far involved intricate statistical analyses. This study reports average chondrite normalized (CN)‐REE signatures for important U deposit types worldwide, which are then employed to evaluate U ore paragenesis using a simple linear regression analysis. This technique provides a straightforward method that can aid in determining the deposit type of U ores based on their REE abundances, and combined with other forensic indicators (e.g. radiogenic isotope signatures) can provide essential provenance information for nuclear materials.